2017
DOI: 10.1016/j.lindif.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the usual cognitive suspects: The importance of speechreading and audiovisual temporal sensitivity in reading ability

Abstract: The aim of this study was to clarify whether audiovisual processing accounted for variance in reading and reading-related abilities, beyond the effect of a set of measures typically associated with individual differences in both reading and audiovisual processing. Testing adults with and without a diagnosis of dyslexia, we showed that-across all participants, and after accounting for variance in cognitive abilities-audiovisual temporal sensitivity contributed uniquely to variance in reading errors. This is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 112 publications
(115 reference statements)
2
17
0
Order By: Relevance
“…In particular, others have found that DD might be associated with more general audio–visual integration processes. For example, Harrar et al (2014) showed that dyslexics have problems with multisensory integration of simple non-linguistic stimuli, Francisco et al (2017) showed a correlation between reading errors and audiovisual temporal sensitivity for speech and non-speech stimuli, and Widmann et al (2012) showed that dyslexic children did not integrate visual symbolic and auditory sensory information into a unitary audiovisual object representation (though see Widmann et al, 2014 ). Of relevance for the present study, it remains to be examined whether individuals with DD might have more subtle integration problems with auditory and lipread speech than we could observe here ( De Gelder and Vroomen, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, others have found that DD might be associated with more general audio–visual integration processes. For example, Harrar et al (2014) showed that dyslexics have problems with multisensory integration of simple non-linguistic stimuli, Francisco et al (2017) showed a correlation between reading errors and audiovisual temporal sensitivity for speech and non-speech stimuli, and Widmann et al (2012) showed that dyslexic children did not integrate visual symbolic and auditory sensory information into a unitary audiovisual object representation (though see Widmann et al, 2014 ). Of relevance for the present study, it remains to be examined whether individuals with DD might have more subtle integration problems with auditory and lipread speech than we could observe here ( De Gelder and Vroomen, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, other studies in school-aged children report no distinct differences between dyslexic and non-dyslexic readers in the identification of speech based on visual cues from talking faces alone or lip-reading but instead suggest a unique impairment in auditory categorization (Baart et al, 2012 ). Still others (Francisco et al, 2017a , b ) find that for adult university students with dyslexia, lip-reading ability uniquely contributes to variance in phonological awareness, with those who score lower on phonological awareness (more severely impaired) being also better lip-readers. This finding seems to support the claim that increased reliance on visual speech may be a compensatory mechanism when processing auditory speech alone is problematic (Francisco et al, 2017a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Still others (Francisco et al, 2017a , b ) find that for adult university students with dyslexia, lip-reading ability uniquely contributes to variance in phonological awareness, with those who score lower on phonological awareness (more severely impaired) being also better lip-readers. This finding seems to support the claim that increased reliance on visual speech may be a compensatory mechanism when processing auditory speech alone is problematic (Francisco et al, 2017a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Hearing and vision affect most learners with dyslexia. As the main mechanism of dyslexia, speech binding defects may be a potential cause of more basic audiovisual processing defects [18].…”
Section: Featuresmentioning
confidence: 99%